KINERJA APARATUR PEMERINTAH PADA SEKRETARIAT KANTOR DINAS TANAMAN PANGAN, HORTIKULTURA DAN PERKEBUNAN KABUPATEN SIGI - Borahima, Nadiah Rizmala (Katalogis, 2020)
The objectives of this research are: (1) to find out the effectiveness of the performance function of public services in the Secretariat Public Relations Division of Sigi Regency (2) to find out the inhibiting and supporting factors and alternative solutions. The basis of the research is a survey and the type was qualitative descriptive. The informants totaled 6 people consisting of officials/employees at the Secretariat of the Office of Food Crops, Horticulture and Plantation of Sigi Regency who were selected purposively. The data were collected through observation, interview and documentation then analyzed through qualitative analysis. The results of the research show that the performance of apparatus in the Secretariat in carrying out the job is very good but still not optimal due to the lack of communication and coordination with the fields so that the implementation of the work seemed long, and there was still discrimination in the fields, this can be seen from the time of completion of the work and the level of satisfaction of the apparatus themselves and also for the public who came to the Office of Food Crops, Horticulture and Plantation of Sigi Regency. If there is the delegation of authority and duties to the apparatus that is given authority, then the work will be able to run effectively. As well as the apparatus it should also be in carrying out their duties always refer to the Standard Operational Procedures that are owned so that the work can be completed promptly and there is no buildup of work on certain people only.